Comparison of treatment efficacy 1 and 2 years after thyroid remnant ablation with 1110 versus 5550 MBq of iodine-131 in patients with intermediate-risk differentiated thyroid cancer. Issue 11 (November 2017) - Aghaei, Atena; Ayati, Narjess; Shafiei, Susan; Abbasi, Bita; Zakavi, S. Rasoul
Abstract : Background: Radioiodine ablation may be associated with improved survival in patients with intermediate-risk follicular cell differentiated thyroid cancer (FCDTC). The aim of this study was to compare ablation efficacy of 1110 versus 5500 MBq of iodine-131 ( 131 I) in FCDTC patients with intermediate risk. Methods: Thirty-nine patients with intermediate-risk FCDTC (T3N0, T1-2N1b and T1-3N1a) were treated with 1110 MBq of 131 I and compared with 43 age-matched and sex-matched patients who received 5550 MBq of 131 I. Patients with invasive histology, extensive lymph node involvement, and preablation thyroglobulin (Tg) of more than 100 ng/ml were excluded from the study. All patients underwent total or near total thyroidectomy with or without lymph node dissection. Response to treatment was evaluated 1 and 2 years after 131 I treatment. Results: We studied four male and 78 female patients, age range 21–69 years. Preablation Tg level was 12.7±17.8 and 15.8±22.6 ng/ml in patients in the low-dose and high-dose groups, respectively ( P =0.48). Anti-Tg antibody level as well as T and N staging were not significantly different in the two groups ( P >0.2). One and 2 years after treatment, an excellent response was noted in 19 and 22 patients in the low-dose group and in 16 and 23 patients in the high-dose group, respectively ( P >0.3). Using logistic regression analysis, preablation Tg was the only significant factor in the prediction of an incomplete response 2 years after therapy. Conclusion: 1110 MBq of 131 I was as effective as 5550 MBq of 131 I in the treatment of FCDTC patients with intermediate risk 1 and 2 years after therapy.